2008
DOI: 10.1111/j.1751-9020.2008.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2005 French Urban Unrests: Data‐Based Interpretations

Abstract: The French 2005 riots in the urban outskirts were the most numerous, widespread and violent France has experienced since the beginning of the 1980s. In The Politics of Collective Violence, Charles Tilly refused the term ‘riot as a scientific idiom’ because it embodies a political judgment rather than an analytical distinction. Authorities and observers label as riots the damage‐going gatherings of which they disapprove, but they use terms like demonstrations, protest, resistance or retaliation for essentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In both France and Sweden a typically broad range of crimes was committed -one study of 208 arrestees in the 93 rd department in France found 40% of offences to be crimes against police officers and 30% destruction or damage to public or private goods -but, unlike England, the most visible target of rioters' violence was motor vehicles. In all, in France over 10,000 cars were destroyed, the bulk by arson (Jobard, 2008). Similarly, Hörnqvist (2014) notes that setting fire to cars in order to attract the police has been a Swedish specialty in certain circles for more than a decade.…”
Section: Naturementioning
confidence: 99%
See 2 more Smart Citations
“…In both France and Sweden a typically broad range of crimes was committed -one study of 208 arrestees in the 93 rd department in France found 40% of offences to be crimes against police officers and 30% destruction or damage to public or private goods -but, unlike England, the most visible target of rioters' violence was motor vehicles. In all, in France over 10,000 cars were destroyed, the bulk by arson (Jobard, 2008). Similarly, Hörnqvist (2014) notes that setting fire to cars in order to attract the police has been a Swedish specialty in certain circles for more than a decade.…”
Section: Naturementioning
confidence: 99%
“…The rioting in France in 2005 broke out initially in Clichy-sous-Bois, which is the poorest locality in Seine-Saint-Denis, the department with the highest unemployment rate in France (Body-Gendrot and Savitch, 2012). The rioting spread to approximately 300 locations, at least 85% of which were identified as one of Zones Urbaines Sensible (Jobard, 2008), characterised by extremely high levels of youth unemployment and a variety of other social problems (Salanié, 2006). In England, of the rioters interviewed in the Guardian/LSE Reading the Riots study who were of working age and not in education, three fifths were unemployed, a pattern confirmed by government data (Ministry of Justice, 2012).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…However, here too Mr Sarkozy refused to concede that the police had any reason for contrition (Schneider, 2008). As Jobard (2008Jobard ( , p. 1290) points out, this atrocity 'acted as a powerful mechanism of boundary activation', fostering a pronounced 'us versus them' mentality throughout the length and breadth of French society ( Jobard, 2008( Jobard, , p. 1290.…”
Section: Trigger and Escalationmentioning
confidence: 99%
“…cit. ; Jobard, 2008;Mucchielli, 2006). In the summer before the rioting occurred, Mr Sarkozy paid a visit to a north Parisian housing estate on which, one day earlier, an 11-year-old boy had been accidentally shot dead in crossfire between local gangs.…”
Section: French Riots Of 2005 Background Conditionsmentioning
confidence: 99%